Os Direitos Humanos e o Sistema Administrativo Social - Grimone, Marcelo José (2017)
The text aims to examine the application of human rights through Administrative Law. A philosophical reflection on the construction, reconstruction and implementation of human rights. And in the course of this reflection we intend to point the limits to the discretion of the administrative act, that is, to understand the administrative function as an instrument to overcome social inequalities and promote the human being. The research also shows that the current Constitution has implemented to the Brazilian justice system a humanistic concept for the traditional positivist law.Positivist dogmatism centered on sanctions has been replaced by decisions that are concerned with the realization of fundamental rights (positive human rights): life, equality, freedom, property and security. The traditional nineteenth-century positivist law, centered on individual bourgeois property and individual subjective law, was superseded at the end of the twentieth century, with the new doctrine of human rights structured by the creation of the International System for the Protection of Human Rights. As a consequence, a new social administrative system is proposed, centered on social rights, participatory and active democracy and the principle of the dignity of the human person. The fundamental rights, inscribed in the caput of article 5 of the Federal Constitution of the Federative Republic of Brazil and the “stone articles”, brought limitations to the Executive Power. Participatory Democracy represented the new proposal for the Democratic and Republican State, based on efficiency, transparency, participation, supervision, and especially on the promotion of public services (health and education). And for this Thesis, the realization of the principle of the dignity of the human person means the promotion of the right to sustainable development and socioeconomic development. Therefore, the contemporary social and humanistic administrative system means overcoming positive and aristocratic right founded on the Order (Sanction) and promoting law centered on social promotion. In analyzing and reflecting on human rights, it is evidenced that the Brazilian constitutional system, although influenced by Hans Kelsen's positivism, but with principles centered on the human being, transformed the country's law and promoted the humanization of the Law and society, and developed a social legal system